Pola Makan Dan Stress Dengan Peningkatan Kadar Gula Darah Pasien Diabetes Melitus Tipe II - Lilipory, Mevi (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2023)
Type II diabetes mellitus is a condition where blood sugar in the body is not controlled due to impaired sensitivity of pancreatic ? cells to produce the hormone insulin. Elevated blood sugar levels or hyperglycemia is a condition in which excessive amounts of glucose circulate in the blood plasma.The diet for Type II Diabetes Mellitus sufferers is to help sufferers improve eating habits so that they can control blood glucose levels within normal limits as a result of hyperglycemia or increased blood sugar levels. Stress is one of the factors that influences blood sugar levels in DM sufferers. Psychological and physical stress has a negative impact on controlling diabetes because an increase in stress hormones will increase blood glucose levels, especially if food intake and insulin administration are uncontrolled. The aim of this study was to determine the relationship between diet and stress and increased blood sugar levels in type II diabetes mellitus patients. This research design uses a systematic review type. This systematic review aims to determine the relationship between diet and stress with increased blood sugar levels in type II diabetes mellitus patients. The method used uses a review of articles and nursing journals. The results of various articles and journals show that there is a significant relationship between diet and stress and increased blood sugar levels in type II diabetes mellitus patients. Diet and stress must be controlled more regularly, so that it can reduce blood sugar levels in patients with type II diabetes mellitus. So it is recommended to increase the patient's knowledge in implementing a correct diet and being able to control the patient's stress so that it can help successfully control blood sugar levels under normal circumstances.Keywords: Diet, Stress, Blood Sugar Levels, Type II Diabetes Mellitus